2021
DOI: 10.1111/jav.02702
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal variation in foraging of breeding red‐throated divers

Abstract: Differing environmental conditions can have profound effects on many behaviours in animals, especially where species have large geographic ranges. Seasonal changes or progression through life history stages impose differential constraints, leading to changes in behaviours. Furthermore, species which show flexibility in behaviours, may have a higher capacity to adapt to anthropogenic‐induced changes to their environment. The red‐throated diver (RTD) is an aquatic bird, that is able to forage in both freshwater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 75 publications
(85 reference statements)
0
13
0
Order By: Relevance
“…The limited amount of movement observed in the Icelandic birds likely means molt is occurring in similar locations to the rest of the non‐breeding period locations. This population does still experience some seasonal change though, as they cease spending time in freshwater environments during the non‐breeding season (Duckworth et al, 2021). Our maps showed a westward movement for some birds during the study period (Figure 3a,b), from the northeast to northwest coast of Iceland.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The limited amount of movement observed in the Icelandic birds likely means molt is occurring in similar locations to the rest of the non‐breeding period locations. This population does still experience some seasonal change though, as they cease spending time in freshwater environments during the non‐breeding season (Duckworth et al, 2021). Our maps showed a westward movement for some birds during the study period (Figure 3a,b), from the northeast to northwest coast of Iceland.…”
Section: Discussionmentioning
confidence: 99%
“…All available locations from all individuals within the stated timeframes are used to generate estimates. RTDs from our study populations completed their breeding attempts by mid-late August (Duckworth et al, 2021), but locations shown are from the early winter period (22nd October-31st December) to late winter period (1st January-20th February) to exclude periods where there is still a noticeable impact on locations from the equinox periods. To further exclude any clearly anomalous data points, any points above 75° North were excluded, as often locations extracted when the GLS logger is heavily shaded are pushed to the northernmost degrees of latitude.…”
Section: Me Thodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used the mean rate of descent (1.38 ms −1 ) from Thaxter et al (2010) plus three standard deviations (SD: 0.16 ms −1 ) in order to account for 99% of the error observed and combined this with our sampling rate, resulting in a maximum depth change of 22.32 m within 12 s. Any depth records that exceeded this speed threshold were removed along with any records that exceeded the maximum measuring potential of the TDRs (200 m). All remaining records with a depth greater than 1 m were defined as diving (Duckworth et al 2020, 2021, Dunn et al 2020). Individual dives were characterised as excursions of depth greater than 1m and subsequent return to the surface.…”
Section: Methodsmentioning
confidence: 99%
“…Dives were categorised into foraging bouts, where more than two dives occurred with less than 180 s of surface time between them (Tremblay and Cherel 2000). To determine whether individuals were generally using a benthic or pelagic (mid‐water) foraging strategy, we calculated the proportion of dives that were within the intra‐depth zone (IDZ; Tremblay and Cherel 2000, Duckworth et al 2021). Higher proportions of dives within the IDZ indicate that a more benthic foraging strategy is being used, as dives are likely to have more similar depths when an individual is foraging benthically (Tremblay and Cherel 2000).…”
Section: Methodsmentioning
confidence: 99%